2014
DOI: 10.12691/ajphr-2-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Risky Sexual Behavior among Unmarried Most-at-Risk Young People in Cambodia

Abstract: Background: Recent surveys suggest that adolescents and young adults in Southeast Asian nations are at great risks of sexual reproductive health issues. This study explored factors associated with risky sexual behavior (RSB) among unmarried most-at-risk young people in Cambodia. Methods: A two-stage cluster sampling method was used to select 1,204 boys and 1,166 girls aged 10-24 from 252 hotspots in the capital city and seven provinces. A five-item scale was constructed to measure RSB. All variables were enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 42 publications
2
40
2
Order By: Relevance
“…The studies from different settings also showed that those women who are in multiple sexual relationships are more likely to face several risk factors for HIV and STIs like early sexual debut, longer duration of sexual activity, remaining with a promiscuous partner, concurrent partnership, and sexual harassment. (17)(18)(19)(20)(21)(22) Therefore, introducing Behaviour Change Communication (BCC) programs can be one important aspect to enhance the condom negotiation skills of the Drayang girls. (23,24) However, this study has limitations to understand the underlying factors for low condom use by the Drayang girls thus deserves further research.…”
Section: Underlying Determinantsmentioning
confidence: 99%
“…The studies from different settings also showed that those women who are in multiple sexual relationships are more likely to face several risk factors for HIV and STIs like early sexual debut, longer duration of sexual activity, remaining with a promiscuous partner, concurrent partnership, and sexual harassment. (17)(18)(19)(20)(21)(22) Therefore, introducing Behaviour Change Communication (BCC) programs can be one important aspect to enhance the condom negotiation skills of the Drayang girls. (23,24) However, this study has limitations to understand the underlying factors for low condom use by the Drayang girls thus deserves further research.…”
Section: Underlying Determinantsmentioning
confidence: 99%
“…Many brothels closed down, and transactional sex has shifted to entertainment venues or other informal and hidden settings such as streets and parks. The lines between direct and indirect sex work have become less clear, and an increase in indirect transactional relationships, such as sweethearts, has been documented [3]. …”
Section: Introductionmentioning
confidence: 99%
“…“Sweethearts,” as they are called locally, involve romantic relationships and include normative lack of condom use as displays of trust and intimacy as well as indirect transactional sex through dinner dates, gifts or shopping trips [3]. For FEWs, a sweetheart is typically a boyfriend and/or regular client [4].…”
Section: Introductionmentioning
confidence: 99%
“…This indicating the low understanding of reproductive health knowledge carrying a greater risk of unintended pregnancy. 13 Condom use among Cambodian young men also considered an issue, data shown the decreasing rate of from 26% in 2010 to 18% in 2014. 14 Increased awareness and comprehensive knowledge of Sexually Transmitted Diseases (STD) strategies among young individuals remain limited.…”
Section: Introductionmentioning
confidence: 99%